Sukuk-Linked Waqf: A Systematic Comparative Analysis Of Institutional and Regulatory Frameworks - Tarada Berlian Megananda; Nurul Rahmah Kusuma (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
Waqf is one of the oldest instruments of Islamic philanthropy with substantial economic potential, yet it has historically been managed conservatively as immovable physical assets, limiting its productivity. Sukuk linked waqf has emerged as an Islamic social finance innovation that integrates waqf, particularly cash waqf, with sukuk instruments to generate sustainable returns while preserving the corpus value. This study examines the development, strengths, weaknesses, and potential of sukuk linked waqf in Indonesia through a systematic comparison with Malaysia and Saudi Arabia, two countries with well-established Islamic finance ecosystems. The study adopts a systematic literature review approach informed by the PRISMA protocol, drawing on indexed scholarly publications, official reports of waqf and Islamic capital market authorities, and national regulations from the three countries. The findings indicate that Indonesia, through its Cash Waqf Linked Sukuk (CWLS), possesses a relatively strong regulatory framework and the world's largest Muslim population base, yet still faces low waqf literacy, limited fund mobilization, and fragmented institutional coordination. Malaysia excels in the diversity of waqf-sukuk contract structures (ijarah, musharakah, SRI sukuk) and a mature Islamic capital market framework, though it faces cross-state structural complexity. Saudi Arabia stands out for its historical experience with sukuk al-intifa' in the Zamzam Tower project and modern institutional reform through the General Authority for Awqaf, with competitive waqf investment returns. The study concludes that Indonesia holds enormous annual cash waqf potential that remains far from fully realized, necessitating stronger public literacy, digitalized governance, cross-institutional regulatory harmonization, and lesson-drawing from Malaysia's contractual innovation and Saudi Arabia's investment governance.